Transcriptional, translational, and physiological signatures of undernourished honey bees (Apis mellifera) suggest a role for hormonal factors in hypopharyngeal gland degradation. (February 2016) - Corby-Harris, Vanessa; Meador, Charlotte A.D.; Snyder, Lucy A.; Schwan, Melissa R.; Maes, Patrick; Jones, Beryl M.; Walton, Alexander; Anderson, Kirk E.
Graphical abstract: Highlights: Honey bee nurses care for larvae in the hive by secreting food from their hypopharyngeal glands. Nurses that are deprived of pollen have small hypopharyngeal glands. Small glands are transcriptionally and translationally active compared to large glands. Small glands show signatures of hormone-induced gland apoptosis. Abstract: Honey bee colonies function as a superorganism, where facultatively sterile female workers perform various tasks that support the hive. Nurse workers undergo numerous anatomical and physiological changes in preparation for brood rearing, including the growth of hypopharyngeal glands (HGs). These glands produce the major protein fraction of a protein- and lipid-rich jelly used to sustain developing larvae. Pollen intake is positively correlated with HG growth, but growth in the first three days is similar regardless of diet, suggesting that initial growth is a pre-determined process while later HG development depends on nutrient availability during a critical window in early adulthood (>3 d). It is unclear whether the resultant size differences in nurse HG are simply due to growth arrest or active degradation of the tissue. To determine what processes cause such differences in HG size, we catalogued the differential expression of both gene transcripts and proteins in the HGs of 8 d old bees that were fed diets containing pollen or no pollen. 3438 genes and 367 proteins were differentially regulated due to nutrition. Of the genes and proteins differentially expressed, undernourished bees exhibited more gene and protein up-regulation compared to well-nourished bees, with the affected processes including salivary gland apoptosis, oogenesis, and hormone signaling. Protein secretion was virtually the only process up-regulated in well-nourished bees. Further assays demonstrated that inhibition of ultraspiracle, one component of the ecdysteroid receptor, in the fat body caused larger HGs. Undernourished bees also had higher acid phosphatase activity, a physiological marker of cell death, compared to well-nourished bees. These results support a connection between poor nutrition, hormonal signaling, and HG degradation.